Global health equity - Awele Utomi (Voices in Bioethics, 2020)
During the COVID-19 pandemic, one of the earliest positives some asserted was COVID-19’s status as an “equal-opportunity killer.” The coronavirus does not distinguish between culture, race, class, or country and will infect everyone it can as opposed to diseases that typically infect the most vulnerable in our society. While the vulnerable population might be different based on geographical area, vulnerability typically intersects with socio-economic status and race. Despite the fact that everyone can be affected by this virus, people who are already economically and socially disadvantaged will suffer the pandemic’s greatest burdens.[i] In the 1918 pandemic, in both wealthy and developing countries, disadvantaged groups (lower social classes and oppressed groups) had substantially higher mortality rates than more privileged groups.[ii] Even in the absence of vaccines and antiviral medications, a pandemic has the potential to produce profound inequalities in burdens, both within and across countries.[iii] These burdens affect morbidity and mortality  which are  dependent on the socio-economic status of the individual or community.